Sosialisasi Pendidikan Karakter Berbasis Pancasila di SD Negeri 004 Babulu - Imam Arrywibowo; Muhammad Dede Lajuardi Saputra; Raihan Satria W.; Nita Afianti; Windy Eka Ramadhani; Muhammad William H.; Tiara Manda A.; Nita Julita; Roslin Siregar; Yayang Chandrakusuma; Seli Seli (Abdimas Universal, 2024)
Pancasila is the philosophy of the Indonesian nation which is a guideline for behavior designed in accordance with the culture of the Indonesian nation which has eastern customs. So it is important for Indonesian people to practice the values of Pancasila. Elementary school students' lack of knowledge about Pancasila and students' low awareness of implementing Pancasila values is the urgency of Pancasila as a state ideology. For this reason, the service team carries out socialization of Pancasila-based character education to elementary school students. The service method used is field observation and studying phenomena directly. This socialization is intended for students at SD Negeri 004 Babulu. In this activity the methods used are presentation of material, short discussion and documentation. This Pancasila-based character education socialization activity aims to develop students who have noble character, character and integrity in accordance with the values contained in Pancasila. The results obtained from this service are increasing students' knowledge about Pancasila, forming students' character based on Pancasila, instilling Pancasila values and making students aware of how to apply Pancasila in everyday life.